Macronutrient Intake Influences the Effect of 25-Hydroxy-Vitamin D Status on Metabolic Syndrome Outcomes in African American Girls. (25th June 2012) - Newton, Anna L.; Hanks, Lynae J.; Ashraf, Ambika P.; Williams, Elizabeth; Davis, Michelle; Casazza, Krista
Abstract : The objectives were to determine the effect of macronutrient modification on vitamin D status and if change in 25-hydroxy-vitamin D concentration influences components of metabolic syndrome in obese African American girls. Methods . Five-week intervention using reduced CHO (43% carbohydrate; 27% fat: SPEC) versus standard CHO (55% carbohydrate; 40% fat: STAN) eucaloric diet. Subjects were 28 obese African American females, aged 9–14 years. Dual energy X-ray absorptiometry and meal test were performed at baseline and five weeks. Results . Approximately 30% of girls had metabolic syndrome. Serum 25OHD increased in both groups at five weeks [STAN: 20.3 ± 1.1 to 22.4 ± 1.1 (P < 0 .05 ) versus SPEC:16.1 ± 1.0 to16.8 ± 1.0 (P = 0.05 )]. The STAN group, increased 25OHD concentration over five weeks (P < 0.05 ), which was positively related to triglycerides (P < 0.001 ) and inversely associated with total cholesterol (P < 0.001 ) and LDL (P < 0.001 ). The SPEC group, had increase in 25OHD (P = 0.05 ), which was positively related to fasting insulin (P < 0.001 ) and insulin sensitivity while inversely associated with fasting glucose (P < 0.05 ). The contribution of vitamin D status to metabolic syndrome parameters differs according to macronutrient intake. Improvement in 25OHD may improve fasting glucose, insulin sensitivity, and LDL; however, macronutrient intake warrants consideration.